PERANCANGAN FASILITAS PENYIMPANAN MATERIAL PADA PT BRINJUTAMASAMUDRA BATAM - Turnip, Fernando Putra; Sirait, Ganda (LPPM Universitas Putera Batam, 2026)
Industrial growth in Batam City has increased rapidly, ranging from small to large scale industries, creating high levels of productivity activity. Ideally, companies must plan proper storage systems to support smooth operations. However, PT Brinjutamasamudra Batam still faces problems related to inadequate storage of tools and materials, which causes delays in work completion, difficulties for employees in accessing equipment, and potential safety risks. The company, located in Batu Aji, specializes in metal fabrication services with a primary focus on stainless steel materials. This research aims to design ergonomic storage facilities for tools and materials that match available space and storage capacity requirements. The study applies Quality Function Deployment and anthropometric approaches with 20 respondents from the turning and welding departments. Data were collected through questionnaires distributed to employees. The results produce a storage cabinet design adjusted to workers’ body characteristics using defined ergonomic parameters. The study concludes that well-organized storage cabinets, designed according to usage frequency, worker needs, and material capacity, are essential to optimize space utilization, improve efficiency, reduce work delays, and support safer and more effective industrial operations. These improvements ultimately enhance employee comfort, productivity, coordination, workflow consistency, equipment protection, and overall operational performance within the manufacturing environment